Revisiting smoking bans in restaurants: Canadian employees perspectives. (April 2015) - Jackson, Leonard A; Taylor, Marcia
The issue of smoking in restaurants and other food service outlets continues to be hotly debated, especially with the bourgeoning interest in, and use of electronic cigarettes. While hospitality research has focused on restaurateurs' and consumers' attitude toward smoking bans in restaurants, employees' views have been virtually ignored. This study examines restaurant employees' attitudes toward smoking bans in two restaurant segments—the coffee and doughnut segment and the family style-dining segment. Findings suggest that employees' attitudes toward smoking bans are largely related to their smoking status. Nonsmokers are generally in favor of smoking bans while smokers are generally in opposition. Overall, it was found that participants from both segments prefer a nonsmoking work environment.